The Meaning of the Poem Sumbawa Horse by Dinullah Rayes: A Review of Riffaterre's Semiotics - Diana, Jumianti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to express the meaning of horses for the people of Sumbawa through the poem